1995
DOI: 10.1006/dbio.1995.8042
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Role for the Heterotrimeric G Protein Goαin a Migratory Population of Embryonic Neurons

Abstract: The heterotrimeric G proteins are an extended family of guanyl nucleotide-binding proteins that serve essential functions in the mature nervous system but whose contributions to neuronal development remain poorly understood. We have investigated the potential role of one specific G protein, Go(alpha), in the control of neuronal migration. During embryogenesis of the moth, Manduca sexta, an identified population of undifferentiated neurons (the EP cells) migrate along sets of visceral muscle bands to form part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 0 publications
8
43
0
Order By: Relevance
“…The migration of neurons has been widely described in vertebrates (Hatten, 1999) but is less common in insects [e.g., migration of aCC and pCC in the grasshopper CNS (Bastiani et al, 1986) and of the enteric neurons (Horgan et al, 1994;Haase and Bicker, 2003)]. We report for the first time neuronal migration in the peripheral nervous system of Drosophila.…”
Section: Sensory Neurons Relocate By Migrating On the Body Wallmentioning
confidence: 80%
“…The migration of neurons has been widely described in vertebrates (Hatten, 1999) but is less common in insects [e.g., migration of aCC and pCC in the grasshopper CNS (Bastiani et al, 1986) and of the enteric neurons (Horgan et al, 1994;Haase and Bicker, 2003)]. We report for the first time neuronal migration in the peripheral nervous system of Drosophila.…”
Section: Sensory Neurons Relocate By Migrating On the Body Wallmentioning
confidence: 80%
“…At the end of each experiment, the preparations were re-dissected to expose the ENS and immunostained with anti-MsFas II, using the ABC HRP kit from Vector Laboratories (Burlingame, CA). This procedure allowed the EP cells and their processes to be visualized unambiguously (Horgan et al, 1995;Wright and Copenhaver, 2000;Coate et al, 2007). The extent of EP cell migration, axon outgrowth, and number of midline crossover events was then analyzed using photomicrographic and camera lucida techniques (Wright et al, 1999;Wright and Copenhaver, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…6, 7). Previous studies showed that these midline cells can be distinguished by a variety of antigenic markers (Horgan et al, 1995;and unpublished data), but their identity and function remained unclear. The histological and electron microscopic analysis presented in this paper (Fig.…”
Section: A Possible Role For Msephrin-mseph Receptor Interactions In mentioning
confidence: 98%
“…Dissected embryos were fixed for 1 hr in PBS (pH 8.0) plus 4% paraformaldehyde (electron microscopy grade; Electron Microscopy Sciences), rinsed, and incubated with the riboprobes (1:100 -1:250 in hybridization buffer) overnight at 60ºC. After extensive rinsing, bound probes were detected using an alkaline phosphatase (AP)-conjugated anti-digoxigenin antibody (1:2000, Roche) and NBT/BCIP substrates (Bio-Rad; Hercules, CA; Horgan et al, 1995).…”
Section: Detection Of Msephrin and Mseph Receptor Mrnamentioning
confidence: 99%